2011
DOI: 10.1016/j.bpc.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A biophysical model of intracellular distribution and perinuclear accumulation of particulate matter

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A C C E P T E D M A N U S C R I P T ACCEPTED MANU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…These lipids droplets are hypothesized to sequester toxicants in order to protect cells from unwanted toxicity. This hypothesis is supported by various in vitro studies on engineered nanoparticles that consistently show sequestration of nanoparticles in cytoplasmic bodies (which may include lipid droplets) in human alveolar cells, primary monocytes, and lung epithelial and monocyte‐derived macrophages from pulmonary cells [Lee et al, ; Rivolta et al, ; Sund et al, ]. These studies, together with the current analysis of whole air exposure, suggest that exposure to PM in urban/industrial air triggers changes in the transcription of genes implicated in lipid droplet formation.…”
Section: Resultssupporting
confidence: 63%
“…These lipids droplets are hypothesized to sequester toxicants in order to protect cells from unwanted toxicity. This hypothesis is supported by various in vitro studies on engineered nanoparticles that consistently show sequestration of nanoparticles in cytoplasmic bodies (which may include lipid droplets) in human alveolar cells, primary monocytes, and lung epithelial and monocyte‐derived macrophages from pulmonary cells [Lee et al, ; Rivolta et al, ; Sund et al, ]. These studies, together with the current analysis of whole air exposure, suggest that exposure to PM in urban/industrial air triggers changes in the transcription of genes implicated in lipid droplet formation.…”
Section: Resultssupporting
confidence: 63%
“…The other possibility is that NP uptake occurs by passive processes and the intracellular trafficking utilizes some energy gradients preexisting inside the cells, due to cell structure itself (cytoskeleton). 37 In other words, NP management may either amplify the cell request for energy or saturate the preexisting routes. These aspects must be taken into consideration regardless of the widespread idea of cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…According to the physicochemical characteristics of the nanocarrier and the nature of the target cells, two main internalization pathways may occur: either a non-energy-dependent interaction with plasma membrane 21,37 or the energy-dependent, endocytotic pathways 4 (see Figures 1 and 2). As far as the non-energy-dependent pathway is concerned, we have demonstrated that coumarin solid-lipid NPs (SLNs) interact with the plasma membrane after a few minutes of exposure.…”
Section: Nanoparticle Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…45 Velasco-Velázquez et al 46 demonstrated that the coumarin derivative 4-hydroxycoumarin was able to disorganize cytoskeletal actin in B16F10 melanoma cells without altering its gene expression. Moreover, recently it was shown 47 that the fluorophore coumarin-6 coupled with solid lipid nanoparticles was able to penetrate in A30 human alveolar cells and spread out in the cytoplasm depending on the actin cytoskeletal structure, suggesting the possible physicochemical affinity and the consequent direct interaction between coumarin compounds and actin. All these evidences confirmed our results and encouraged us to propose the following action model of ND + C treatment in B16F10 cells ( Figure S3): NDs regulate the internalization of citropten in the cells, allowing C to reach low intracellular concentration not sufficient to induce apoptosis.…”
mentioning
confidence: 99%